Nepalese Capital Market: Issues and Challenges - Koirala, Parashar; Bajracharya, Pushkar (NRB Economic Review, 2004)
Establishment of the Nepal Stock Exchange (NEPSE) market opened an avenue to investors, both large and small, to invest in the enterprise sector and participate in the secondary market. Despite apprehensions of many, the secondary market proved to be successful, with both the entrepreneurs and the investors showing earnest acceptance and participation in the process. However, the performance of stock exchange during the latter years gives only a mixed result. The enthusiasm did not last long as, after 2000/01, both the size and trend began to shrink. The NEPSE index came down to 204 in 2002/03 from a peak of 360 in 1999/00. The transaction volume came down to about Rs 575 million in 2002/03 compared to Rs 2344 million in 2000/01. This scenario, despite increasing number of listed securities and scrips, is not a favourable situation. Generally, the problem is attributed to the prevailing politico- economic situation. No doubt, it is true to a large extent but the problem is not confined to the present situation alone. The management of the companies and the attitude of the board of directors and intermediaries are to blame a lot. The actors of financial markets are loosely tied together from legal provisions, which are not effectively implemented. As the financial institutions predominate the market, it has not been able to diversify. Increasing problems noted with the corporate governance, transparency and disclosure have seriously dented the Nepalese capital market. The Board mainly acts as a superfluous body trying to fulfill formalities rather than seriously attending to corporate governance. The result has been poor security to investors, particularly minority shareholders, who are not fully aware of the risk and return considerations. Hence, to make the stock exchange a vehicle of growth, initiatives must be taken to protect investors, improve corporate governance and make the companies operate in a conducive and transparent manner.